Community of Practice on Soil Health in Nature+ - Kaushal, Manoj (2023)
Soil health is the inherent ability of soil to function for agroecosystems productivity and environmental sustainability. With the limitations of nutrients, degradation, water conservation, extreme conditions due to climate change and mounting pressure to produce food, soil health is critical for human existence and thus gaining global debates. Developing and implementing the strategies and action plans to ensure soil health and fertility is also the strategic priority by framework for action biodiversity for food and agriculture. Both globally and at NARS level efforts are leveraged for research and development on soil health but while working with small holder farmer’s (SHF) and other stakeholder’s we get the message: SHF- maintain and rebuild healthy soils required for continuous productivity and long term sustainability, stakeholder’s- apart from good crop/seed and varietal assess, we need innovations to expand soil health into conventional agriculture practices. With the current progress, stakeholder’s recognition is of much importance that allows adaptive capacity on soil health practices in building countries design and implement strategies contributing to healthy and nutritious food availability as well as the income generation.